Geosynthetics Materials: Recent Advancements for ground Improvements. - Kumar, Tarun (IJRDO-Journal of Applied Science, 2015)
Geosynthetics are man-made materials used to improve Groundconditions.. The material properties of geosynthetics are important to their use in variousapplications like canal lining, used for increasing bearing capacity and permeability of soil,reducing settlement of soil, soil reinforcement, soil stabilization etc.Geosynthetics havebecome well established construction materials for geotechnical and environmentalapplications in most parts of the world. This paper focuses on recent advances ongeosynthetics products, applications and design methodologies required for reinforcingsoil, ground improvement and environmental protection work.